Antifungal Susceptibility to Amphotericin B, Fluconazole, Voriconazole, and Flucytosine in Candida Bloodstream Isolates from 15 Tertiary Hospitals in Korea - Jung, Sook-In (The Korean Society for Laboratory Medicine, 2012)
The in vitro antifungal susceptibility of 636 Candida bloodstream isolates collected from 15 tertiary hospitals in Korea was determined using the Vitek-2 yeast susceptibility system (bioMérieux, France). Overall susceptibility rates were 98.1%, 95.9%, 99.1%, and 97.3% for amphotericin B, fluconazole, voriconazole, and flucytosine, respectively. The results show that the rates of resistance to 4 antifungal drugs remain low among Candida bloodstream isolates in Korea.